Amanitine poisoning - cases, management, therapy results - Kubicka, Magdalena; Wilk, Joanna; Dębiec, Paweł; Cholewa, Krystian; Makarewicz, Magdalena; Szymańska, Adrianna (Journal of Education, Health and Sport, 2023)
Mushroom poisoning continues to be a serious clinical problem. The most serious are intoxications with mushrooms containing cytotropic toxins with predominant injury of liver, kidneys and heart. The toxic properties of the phalloides are mainly due to α-amanitin, which is an inhibitor of RNA polymerase II. The clinical course of poisoning can be divided for 4 periods. The asymptomatic period usually lasts 6-24 hours after mushroom consumption. Then the period of the gastrointestinal disorder lasting on average 12-24 hours. The second latency period with apparent improvement of the patient’s general condition lasting 12-24 hours is subjected to the stage, during which biochemical markers of hepatocyte activity appear. After a few days (usually on the 4-5th day) from poisoning, kidney function may occur (oliguria or anuria), and circulatory system disorders may also occur. Death usually occurs between 4-16 days after poisoning. The treatment of poisoning with amanita phalloides includes a number of procedures, including rapid removal of toxins, blocking the penetration of amatoxins into the hepatic cell, compensation of systemic metabolic disorders, and extracorporeal support of liver function.